The legend of Cen Cemana / Sharina Saad ... [et al.] - Saad, Sharina; Mohammed, Syakirah; Ahmad@Ahmad Jali, Fathiyah; Abu Hassan, Anita (Universiti Teknologi MARA Kedah, 2022)
The Legend of Cen Cemana depicts the evil ogre which roams in the deep jungle of the Semai. She has the habit of attentively watching and observing children who come to play near the forest. She will approach them and give them sweet fruits before inviting the innocent children to her wooden house in the jungle. She would feed the children and put them to sleep. Soon enough the children will realize Cen Cemana's bad intention but since they are in captivity they can no longer leave Cen Cemana's house. When it is time to feast Cen Cemana will kill these unfortunate children and eat them. The Semai believe that" Strangers are dangerous" and will always remind their children about Puteh's tragedy from generation to generation orally. In the story of 'The Legend of Cen Cemana ', The elderly Semai advises children to avoid boastful acts and never to trust strangers. In the story when the children did not listen to the elderly advice to go to the forest unaccompanied, they would be in trouble. The values from The Legend of Cen Cemana's story are still relevant to the present day.